2019
DOI: 10.1186/s12909-019-1691-y
|View full text |Cite
|
Sign up to set email alerts
|

Swedish doctors choice of medical speciality and associations with cultural capital and perceived status: a cross-sectional study

Abstract: Background Many western countries have problems recruiting and retaining medical specialists. In Sweden there is a lack of primary care doctors and psychiatrists. Despite much research on the topic the shortage remains. We therefore set out to analyse choice of medical speciality using Bourdieu’s theoretical concepts; cultural capital, social background and perceived status. Methods A cross-sectional questionnaire-based study of 399 alumni from the Medical School at Kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…Our analysis showed that the MPs in general practice were not in the specialty for its status. These results are congruent with research that has shown that domestically trained physicians in general practice also rank the specialty as having low status [ 38 ]; that they are aware of their specialty’s low status but still are satisfied with their choice [ 8 ]. Not all physicians strive for high-prestige specialties, like surgery [ 8 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our analysis showed that the MPs in general practice were not in the specialty for its status. These results are congruent with research that has shown that domestically trained physicians in general practice also rank the specialty as having low status [ 38 ]; that they are aware of their specialty’s low status but still are satisfied with their choice [ 8 ]. Not all physicians strive for high-prestige specialties, like surgery [ 8 ].…”
Section: Discussionsupporting
confidence: 86%
“…The survey was divided into three parts: survey instrument items earlier used by Bexelius et al ( 2016 ) and Olsson et al ( 2019 ), the Big Five Inventory (BFI; John & Srivastava, 1999 ), and Measure of Health‐Related Quality of Life (RAND‐36; Hays et al, 1993 ).…”
Section: Methodsmentioning
confidence: 99%
“…The survey instrument items earlier used by Bexelius et al ( 2016 ) and Olsson et al ( 2019 ) were modified to fit SN students and the aims of this study and can be viewed in Appendix S1 . Bexelius et al ( 2016 ) and Olsson et al ( 2019 ) survey was focused on physicians' education; therefore, we needed to adapt the content of the questions to fit the nurse's education instead. For part A.1, no major modifications were needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in many countries too few students are interested in a specialisation in family medicine, psychiatry or Gynecology, which will create a future shortage of physicians in these specialties [1][2][3][4][5][6] . Factors that are taken into account are the research possibilities [3,7], the perceived status of the discipline [8,9] and the patient population [7,10]. This problem is not new -in the 1960s, too few medical students were interested in a career as a general practitioner as well [11].…”
Section: Introductionmentioning
confidence: 99%